Orientacje sprawcze i wspólnotowe współczesnej młodzieży - Peret-Drążewska, Paulina (Kultura-Społeczeństwo-Edukacja, 2014)
The primary aim of the article is a discussion on the youth's orientation in the social aspects of life in theoretical and empirical perspective. The research subject raised in this article is to show the image of the today’s youths from the perspective of peers by the designation of some aspects, especially social orientations, that are being only fragments of the necessary conditions to seize the situation of young people.